Proper modulation of AHR signaling is necessary for establishing neural connectivity and oligodendrocyte precursor cell development in the embryonic zebrafish brain - Martin, Nathan R.; Patel, Ratna; Kossack, Michelle E.; Tian, Lucy; Camarillo, Manuel A.; Cintrón-Rivera, Layra G.; Gawdzik, Joseph C.; Yue, Monica S.; Nwagugo, Favour O.; Elemans, Loes M. H.; Plavicki, Jessica S. (Frontiers in Molecular Neuroscience, 2022)
2,3,7,8-tetrachlorodibenzo-[p]-dioxin (TCDD) is a persistent global pollutant that exhibits a high affinity for the aryl hydrocarbon receptor (AHR), a ligand activated transcription factor. Epidemiological studies have associated AHR agonist exposure with multiple human neuropathologies. Consistent with the human data, research studies using laboratory models have linked pollutant-induced AHR activation to disruptions in learning and memory as well as motor impairments. Our understanding of endogenous AHR functions in brain development is limited and, correspondingly, scientists are still determining which cell types and brain regions are sensitive to AHR modulation. To identify novel phenotypes resulting from pollutant-induced AHR activation and ahr2 loss of function, we utilized the optically transparent zebrafish model. Early embryonic TCDD exposure impaired embryonic brain morphogenesis, resulted in ventriculomegaly, and disrupted the neural connectivity in the optic tectum, habenula, cerebellum, and olfactory bulb. Altered neural network formation was accompanied by reduced expression of synaptic vesicle 2. Loss of ahr2 function also impaired nascent network development, but did not affect gross brain or ventricular morphology. To determine whether neural AHR activation was sufficient to disrupt connectivity, we used the Gal4/UAS system to express a constitutively active AHR specifically in differentiated neurons and observed disruptions only in the cerebellum; thus, suggesting that the phenotypes resulting from global AHR activation involve multiple cell types. Consistent with this hypothesis, we found that TCDD exposure reduced the number of oligodendrocyte precursor cells and their derivatives. Together, our findings indicate that proper modulation of AHR signaling is necessary for the growth and maturation of the embryonic zebrafish brain.